Keep your head up - Correlation between visual exploration frequency, passing percentage and turnover rate in elite football midfielders - Phatak, A.; Gruber, M. (Sports, 2019)
Statistical analysis of real in-game situations plays an increasing role in talent identification and player recruitment across team sports. Recently, visual exploration frequency (VEF) in football has been discussed as being one of the important performance-determining parameters. However, until now, VEF has been studied almost exclusively in laboratory settings. Moreover, the VEF of individuals has not been correlated with performance parameters in a statistically significant number of top-level players. Thus, the objective of the present study was to examine the relationship between VEF and individual performance parameters in elite football midfielders. Thirty-five midfielders participating in the Euro 2016 championship were analyzed using game video. Their VEF was categorized into scans, transition scans, and total scans. Linear regression analysis was used to correlate the three different VEF parameters with the passing percentage and the turnover rate for individual players. The linear regression showed significant positive correlations between scan rate (p = 0.033, R2 = 3.0%) and total scan rate (p = 0.015, R2 = 4.0%) and passing percentage but not between transition scan rate and passing percentage (p = 0.074). There was a significant negative correlation between transition scan rate and turnover rate (p = 0.023, R2 = 3.5%) but not between total scan rate (p = 0.857) or scan rate (p = 0.817) and turnover rate. In conclusion, the present study shows that players with a higher VEF may complete more passes and cause fewer turnovers. VEF explains up to 4% of variance in pass completion and turnover rate and thus should be considered as one of the factors that can help to evaluate players and identify talents as well as to tailor training interventions to the needs of midfielders up to the highest level of professional football.